No differences in knee kinematics between active and passive flexion-extension movement: an intra-operative kinematic analysis performed during total knee arthroplasty - Alberto Grassi; Nicola Pizza; Nicola Francesco Lopomo; Maurilio Marcacci; Michele Capozzi; Giulio Maria Marcheggiani Muccioli; Francesca Colle; Stefano Zaffagnini (Journal of Experimental Orthopaedics, 2020)
Abstract Purpose The objective of the present study was to acquire and compare by the use of a navigation system the intra-operative flexion-extension movement of the knee performed actively by the patient and passively by the surgeon before and after a total knee arthroplasty (TKA) implantation. Methods A cohort of 31 patients with primary knee osteoarthritis (OA), candidate for TKA underwent intra-operative kinematics assessment with a commercial navigation system before and after the definitive implant positioning of a Cruciate Retaining (CR) Mobile Bearing (MB) prostheses. The kinematical data were acquired while surgeon performed the flexion-extension movement (passive ROM - pROM), and while the patient performed it (active ROM - aROM). Differences between pre- and post- implantation and between active and passive motions, were statistically analyzed using paired Student t-tests (p = 0.05). Results No statistically significant difference were found between aROM and pROM with paired Student t-test regarding internal-external rotation and anterior-posterior translation of the femoral component with respect to the tibia during flexion-extension movement before and after TKA implant (p > 0.05). Conclusions Active muscle contraction seems to not significantly affect TKA kinematics. The ROM performed by the surgeon during operation resemble the movement actively performed by the patient. The clinical relevance of this study further supports the use of CAS system in performing intra-operative analysis concerning knee biomechanics.